Tasawwuf moderation in higher education: Empirical study of Al-Ghazālī’s Tasawwuf contribution to intellectual society - Yedi Purwanto; Aep Saepudin; Shofaussamawati; Mohammad Rindu Fajar Islamy; Didin Baharuddin (Cogent Social Sciences)
In Indonesia, Tasawwuf is not a new phenomenon. Religious practices that purifying the heart have been deeply rooted in religious traditions, from academics, Islamic boarding schools, and universities. However, lately, demands to disband the authority of Tasawwuf from Islamic teachings have come from reformist groups fronted by Salafi Jihadi, where the basis of their argument is based on the prevalence of Sufi practices that are too far-fetched, irrational, and even tend to injure the theological aspects. Amid the vortex of debate dialogue between reformists and traditionalists in the area of tasawwuf, a community emerged which they called “wasatiyyah” or moderate, where the main focus of their mission was to bring together different points of view in a wiser portion in responding to them. This article closely examines the contribution of Muslim intellectual “Tasawwuf Moderation” through Abū Hāmid Al-Ghazālī (who died in the 5th century) and its implications for Indonesian society’s culture in general to the discourse of socio-religious movements of intellectuals in higher education.